Pragmatism and inquiry selected essays - Levi, Isaac, 1930- (Oxford : Oxford University Press, 2013)
This volume presents a series of essays on the nature of intellectual inquiry: what its aims are and how it operates. Isaac Levi draws upon the work of the American Pragmatists C. S. Peirce and John Dewey to investigate what justifies change in belief.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Inquiry (Theory of knowledge); Pragmatism